Consensus-based recommendations for the management of juvenile dermatomyositis. Issue 2 (11th August 2016) - Enders, Felicitas Bellutti; Bader-Meunier, Brigitte; Baildam, Eileen; Constantin, Tamas; Dolezalova, Pavla; Feldman, Brian M; Lahdenne, Pekka; Magnusson, Bo; Nistala, Kiran; Ozen, Seza; Pilkington, Clarissa; Ravelli, Angelo; et al.
Abstract : Background: In 2012, a European initiative called S ingle H ub and A ccess point for pediatric R heumatology in E urope (SHARE) was launched to optimise and disseminate diagnostic and management regimens in Europe for children and young adults with rheumatic diseases. Juvenile dermatomyositis (JDM) is a rare disease within the group of paediatric rheumatic diseases (PRDs) and can lead to significant morbidity. Evidence-based guidelines are sparse and management is mostly based on physicians' experience. Consequently, treatment regimens differ throughout Europe. Objectives: To provide recommendations for diagnosis and treatment of JDM. Methods: Recommendations were developed by an evidence-informed consensus process using the European League Against Rheumatism standard operating procedures. A committee was constituted, consisting of 19 experienced paediatric rheumatologists and 2 experts in paediatric exercise physiology and physical therapy, mainly from Europe. Recommendations derived from a validated systematic literature review were evaluated by an online survey and subsequently discussed at two consensus meetings using nominal group technique. Recommendations were accepted if >80% agreement was reached. Results: In total, 7 overarching principles, 33 recommendations on diagnosis and 19 recommendations on therapy were accepted with >80% agreement among experts. Topics covered include assessment of skin, muscle and major organ involvement and suggested treatment pathways. Conclusions: The SHARE initiative aims to identify best practices for treatment of patients suffering from PRD. Within this remit, recommendations for the diagnosis and treatment of JDM have been formulated by an evidence-informed consensus process to produce a standard of care for patients with JDM throughout Europe.